Condição periodontal e biomarcadores séricos em indivíduos transplantados renais - GOMES, Samira Vasconcelos (2018)
Studies associate periodontal disease with chronic kidney disease (CKD). The objective of this study was to analyze the possible relationship between periodontal condition and serum biomarkers (calcium, phosphorus, sodium, potassium, hemoglobin, hematocrit, leukocytes, platelets, fasting glucose, triglycerides, total cholesterol, glutamic-oxalacetic transaminase, glutamic-pyruvic transaminase, creatinine and urea) in renal transplant recipients. Thirty seven renal transplants between 2016 and 2017 of the University Hospital of the Federal University of Maranhão with at least six months of transplantation were included in this cross-sectional study. The periodontal condition was verified by means of the evaluation of periodontal parameters, including probing depth (PD), gingival level (GL) and clinical attachment level (CAL), in six sites, besides the gingival bleeding index (GBI) and visible plaque index (VPI). The individuals were divided into two groups according to the presence of chronic periodontitis (CP), considering at least one site with CAL ≥ 4 mm and PD ≥ 4 mm. Serum biomarkers were obtained from the medical records respecting the maximum interval of seven days between periodontal examination and blood collection. Comparative analysis between groups and correlation analysis between periodontal measurements and serum markers were performed, using SPSS 17.0 (IBM, Chicago, IL, USA), adopting a significance level of 5%. The CP group had a higher mean of leukocytes (P = 0.025). There was an inverse correlation between GBI and sodium (Rs = -0.40, P = 0.040). VPI had a direct correlation with fasting glycemia (Rs = 0.50, P = 0.001) and triglycerides (Rs = 0.35, P = 0.047). There was an inverse correlation between the percentage of sites with CAL > 4 mm and creatinine (Rs = -0.32, P = 0.050). The percentage of sites with PD > 4 mm presented an inverse correlation with hemoglobin (Rs = -0.36, P = 0.027), hematocrit (Rs = -0.42, P = 0.008), and fasting glycemia (Rs = -0.42 ; P = .009). Correlation between serum biomarkers studied and periodontal clinical parameters was found in renal transplant recipients.